AGAMA DALAM PANDANGAN FUTUROLOG - Bakhtiar, Amsal (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2013)
Before modern era, religion became more dominant in daily life of human being because religion institution is the sole authority to dicide either religion aspect or scientifi c one. But in modern era, especially after some inventions of modern science and technology, secular scientist in the West very proud of his intellectual ability to explore the nature. Th ey neglect religion and even accused religion as an opium and illusion. In fact, human being cannot free from believing in Supra Natural Being because even though in the atheist community still respect the spirit of ancestors. Th erefore, every eff ort to attack religion will fail because religion could not separated from basic need of human being and religion is the the sole doctrin of life in hereafter. Naisbitt, a famous futurolog, also declares that the spiritual of religion will become dominant in new era.